Framing Depression - Annemarie Wiedicke; Doreen Reifegerste; Linn Julia Temmann; Sebastian Scherr (European Journal of Health Communication (EJHC), 2022)
Responsibility framing research on health issues typically investigates the attribution of responsibility for causes and treatment options to either the individual or society. However, social epidemiological perspectives also stress the relevance of an individual’s social network and underline that the three levels of responsibility (individual, social network, and society) interact. Given that media portrayals can affect public perceptions, attitudes, responsibility attributions, and emotions, we examined causal and treatment responsibility attributions on these three levels in the media coverage of depression. Our quantitative content analysis of major German print and online news media from 2011 to 2020 (N = 755) shows that responsibility is not only assigned to the individual and societal level, but both to the social network and to interactions between the three levels. Our findings additionally stress that key events may influence the portrayal of responsibility in media coverage, but resulting changes are only short-term.